Coyuntura Económica - Rozo, María Carolina; Castro, Emma Beatriz; Bedoya, Ángela Patricia; Sánchez, Holmes; Aponte, Guillermo (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2010)
Análisis económico